Penguatan Pemahaman Dinamika Perkembangan Remaja : Model Pendampingan Integratif Teori Kohnstamm, Oswald Kroh, dan Jean Piaget - Adelia Adelia; Fadilatul Hikmah; Dini Wardatul Willah; Endah Tri Wisudaningsih (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service addresses the critical struggle of students at SMP Taruna Islam Al-Kautsar (SMP TI Al-Kautsar) to understand the major psychological and emotional changes during adolescence. This lack of clarity often led to confusion and challenges in self-adjustment, pointing out a significant gap in the school's existing guidance support. The main goal was to solve this by creating and implementing an Integrative Mentoring Model (IMM). This model directly explained their developmental stages using three key psychological frameworks: Kohnstamm, Oswald Kroh, and Jean Piaget. We followed a hands-on Participatory Action Research (PAR) method, where 50 adolescent students actively joined six specialized, interactive workshops and group coaching sessions over two weeks. The activity showed clear success, as students displayed much stronger self-awareness regarding their cognitive and emotional growth after the program. They reported increased confidence and began using the developmental theories to better understand their peers and manage their own changes. The IMM effectively translated complex academic concepts into practical life knowledge. This success confirms the IMM as a valuable, theory-backed framework for enhancing student well-being and adaptation in other religious educational settings.